Intramural florid cystic endosalpingiosis of the uterus: A case report and review of the literature - Soyoung Im; Ji-Han Jung; Hyun Joo Choi; Chang Suk Kang (Taiwanese Journal of Obstetrics & Gynecology, 2015)
Objective: We report a case of intramural florid cystic endosalpingiosis in the lower uterine segment of the uterus. Case report: A 43-year-old female presented with vaginal bleeding. Abdominal computed tomography suggested a leiomyoma with cystic degeneration. A total hysterectomy revealed a 4.0 cm × 3.8 cm cystic mass in the lower uterine segment. The cystic space microscopically was lined with a single layer or stratified layer of ciliated columnar cells that resembled tubal epithelium without cytologic atypia. The glandular spaces were surrounded by normal myometrium with no evidence of periglandular endometrial stroma, which was consistent with the diagnosis of florid cystic endosalpingiosis. Conclusion: Florid cystic endosalpingiosis involving the uterus is a rare and clinically unexpected finding; however, it should be considered in the differential diagnosis of a uterine mass.